Yeast adaptation to weak acids prevents futile energy expenditure - Ullah, Azmat; Chandrasekaran, Gayathri; Brul, Stanley; Smits, Gertien J. (Frontiers in Microbiology, 2013)
Weak organic acids (WOAs) are widely used preservatives to prevent fungal spoilage of foods and beverages. Exposure of baker's yeast Saccharomyces cerevisiae to WOA leads to cellular acidification and anion accumulation. Pre-adaptation of cultures reduced the rate of acidification caused by weak acid exposure, most likely as a result of changes in plasma membrane or cell wall composition. In order to adapt to sublethal concentrations of the acids and grow, yeast cells activate ATP consuming membrane transporters to remove protons and anions. We explored to what extent ATP depletion contributes to growth inhibition in sorbic or acetic acid treated cells. Therefore, we analyzed the effect of the reduction of proton and anion pumping activity on intracellular pH (pHi), growth, and energy status upon exposure to the hydrophilic acetic acid (HA) and the lipophilic sorbic acid (HS). ATP concentrations were dependent on the severity of the stress. Unexpectedly, we observed a stronger reduction of ATP with growth reducing than with growth inhibitory concentrations of both acids. We deduce that the not the ATP reduction caused by proton pumping, but rather the cost of sorbate anion pumping contributes to growth inhibition. A reduction of proton pumping activity may reduce ATP consumption, but the resulting decrease of pHi affects growth more. ATP utilization was differentially regulated during moderate and severe stress conditions. We propose that the energy depletion alone is not the cause of growth inhibition during HA or HS stress. Rather, the cells appear to reduce ATP consumption in high stress conditions, likely to prevent futile cycling and maintain energy reserves for growth resumption in more favorable conditions. The mechanism for such decision making remains to be established.